Extraction of Omega-3 Fatty Acid from Jade Perch (Scortum barcoo) Using Enzymatic Hydrolysis Technique - Nur Izzati Iberahim; Yee Chee Hann; Zainab Hamzah; Khairunissa Syairah Ahmad Sohaimi (Indonesian Journal of Chemistry, 2020)
Extraction of omega-3 fatty acid from Jade Perch (Scortum barcoo) using enzymatic hydrolysis techniques are expected to be more economically possible techniques due to the uses of the enzyme with the characteristic of environmentally friendly, reusable and less energy required during large-scale production. Design of Experiments (DOE) was used to study the effect of process parameters such as the concentration of alcalase (0.5–1.5%), temperature (50–70 °C) and pH (6.5–8.5) towards the yield of oil. The findings showed 16.55% of oil yield was extracted from the jade perch under an optimum condition at 50 °C, 6.5 pH with 0.5% of enzyme concentration for 2 h incubation time. The fish oil was then undergone enzymatic concentration of omega-3 FA using lipase from Candida rugosa. The acid value and peroxide value of the fish oil was 71.422 mg KOH/g and 0.799 meq/kg, while the acid and peroxide value of the omega-3 concentrated oil was lower to 49.074 mg KOH/g and 0.399 meq/kg. The FTIR spectrum showed the presence of C–H stretch, =C–H stretch and C=O stretch bond justified the existence of lipids as it presents of alkanes, alkene, and carboxylic acids functional group. At the same time, GC-MS analysis showed the fish oil contains higher total PUFA content and omega-3 fatty acid content than omega-3 concentrated oil.